2015
DOI: 10.3109/13880209.2014.952838
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic mechanism ofCoptis chinensispolysaccharide through its antioxidant property involving the JNK pathway

Abstract: Context: Antidiabetic activity of Coptis chinensis Franch (Ranunculaceae) polysaccharide (CCPW) has been reported. However, its molecular mechanism remains unclear. Objective: An attempt was made to further verify the antidiabetic activity of CCPW on type 2 diabetes mellitus (T2DM) and elucidate the mechanism of antidiabetic activity. Materials and methods: Male Wistar rats were fed with high-fat diet (HFD) and injected with streptozotocin (STZ) to generate a T2DM model. Effects of CCPW on fasting blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Meanwhile, the AGE accumulations and morphological abnormalities in the pancreas and liver were also improved [ 143 ]. It was also reported that the anti-diabetic effect of a water-soluble polysaccharide isolated from CR was achieved through its anti-oxidative effect involving the JNK pathway [ 144 , 145 ]. This water-soluble polysaccharide CCPW-1 could increase glutathione peroxidases, SOD, catalase activities and decrease glutathione and MDA contents while inhibiting JNK expression in high-fat with streptozotocin diet induced diabetic mice.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Meanwhile, the AGE accumulations and morphological abnormalities in the pancreas and liver were also improved [ 143 ]. It was also reported that the anti-diabetic effect of a water-soluble polysaccharide isolated from CR was achieved through its anti-oxidative effect involving the JNK pathway [ 144 , 145 ]. This water-soluble polysaccharide CCPW-1 could increase glutathione peroxidases, SOD, catalase activities and decrease glutathione and MDA contents while inhibiting JNK expression in high-fat with streptozotocin diet induced diabetic mice.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Coptis chinensis Franch, of the Ranunculaceae family, which is commonly known as Huanglian in China, is one of the 50 fundamental herbs used in traditional Chinese medicine (Li, Tsai, Damu, & Wu, ). Coptidis rhizoma, the dried rhizome of C. chinensis , has commonly been prescribed for various clinical effects, such as anti‐diabetic (Jiang et al, ), hypocholesterolemic and hypoglycemic (Yuan, Tu, Ye, & Wu, ), anti‐inflammatory (Choi et al, ; Cui et al, ), antioxidant (Ban et al, ), analgesia (Tjong et al, ) and neuroprotective (Friedemann et al, ) properties. Coptidis rhizoma is known to harbor a diversity of active isoquinoline‐type alkaloids such as berberine, coptisine, epiberberine, palmatine and jatrorrhizine.…”
Section: Introductionmentioning
confidence: 99%
“…The pathologic effects of AGEs are related to their ability to generate reactive oxygen species in addition to auto-oxidation reactions yielding radicals and other reactive intermediates (Lv et al 2014). Therefore, more attention has been paid to polysaccharides with antioxidant potential that may retard the process of AGEs formation by preventing further oxidation of glycation products (Deng et al 2003;Rout & Banerjee 2007;Jiang et al 2015).…”
Section: Introductionmentioning
confidence: 99%